2018
DOI: 10.21831/jptk.v24i2.20005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Problem-Based Learning Model and Motivation toward Learning Outcomes on Network Routing

Abstract: This study explored the effect of problem-based learning and motivation toward learning outcomes of the subject of computer routing network. Computer routing network is part of the subject of computer network design in a computer network engineering class. The purpose of this study was to examine the difference in learning outcomes between students treated with the problems based learning model and treated with direct learning model by considering students’ learning motivation. This study was categorized as qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Teachers' creativity can improve students' ability to think critically in determining learning strategies in several subjects [53]. PBL influences learning learning achievement, motivation, critical thinking skills [54], PBL positively influences student learning outcomes [20], and learning outcomes outing network are taught with PBL better than direct-instruction, and there is motivation interaction and PBL on learning outcomes [20].…”
Section: Learning Outcomementioning
confidence: 99%
“…Teachers' creativity can improve students' ability to think critically in determining learning strategies in several subjects [53]. PBL influences learning learning achievement, motivation, critical thinking skills [54], PBL positively influences student learning outcomes [20], and learning outcomes outing network are taught with PBL better than direct-instruction, and there is motivation interaction and PBL on learning outcomes [20].…”
Section: Learning Outcomementioning
confidence: 99%
“…The learning methods used in learning can also affect students' motivation so that later it impacts the learning outcomes of these students (Ariyanti et al, 2018). Furthermore, research in Iraq concluded that a teacher's learning and teaching model would increase student interest in the lesson (Mustafa, 2018).…”
Section: |mentioning
confidence: 99%
“…In addition, motivation becomes the main key factor contributing in the learning process. Being inspired by some results of the previous studies, the present study is interested to conduct further research on problem-based learning as what have been done by Bashith & Amin (2017), Dharma et al (2020), Ariyanti et al (2018), andAstuti et al (2020). The present study will present different investigation compared to the previous studies since the present study presents an innovative learning model derived from combination of problembased learning and Pancasila student profile.…”
Section: A Introductionmentioning
confidence: 99%
“…Bashith & Amin (2017) and Dharma et al (2020) reported that problem-based learning affected significantly students' critical thinking both senior and vocational high schools. Besides, Ariyanti et al (2018) found out that problembased learning significantly affected learning outcomes of vocational school on their networking routing. In addition, Astuti et al (2020) reported that problem-based learning showed significant effect on students' learning outcomes in elementary schools.…”
Section: A Introductionmentioning
confidence: 99%